1996
DOI: 10.1063/1.361430
|View full text |Cite
|
Sign up to set email alerts
|

Surface photoabsorption study of the effects of growth temperature and V/III ratio on ordering in GaInP

Abstract: Surface photoabsorption (SPA) measurements were used to clarify the Cu–Pt ordering mechanism in Ga0.5In0.5P layers grown by organometallic vapor phase epitaxy. The Cu–Pt ordering is strongly affected by the growth temperature and the input partial pressure of the phosphorus precursor, i.e., the V/III ratio. SPA was used to measure the concentration of [1̄10]-oriented phosphorus dimers on the surface, which are characteristics of the (2×4) reconstruction, as a function of the growth temperature and V/III ratio.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…Here, E g ð0Þ of fully disordered Ga 0.51 In 0.49 P is taken to be 2007 meV at the absolute zero [18] and 2005 meV at 20 K [19]. Theoretically, DE g ¼ E g ð0Þ À E g ð1Þ is 490 meV [18], which is consistent with experimental DE g E471 meV at 20 K [19].…”
Section: Pl From Gainp Epilayers and Gainp/algainp Quantum Wellsmentioning
confidence: 66%
See 1 more Smart Citation
“…Here, E g ð0Þ of fully disordered Ga 0.51 In 0.49 P is taken to be 2007 meV at the absolute zero [18] and 2005 meV at 20 K [19]. Theoretically, DE g ¼ E g ð0Þ À E g ð1Þ is 490 meV [18], which is consistent with experimental DE g E471 meV at 20 K [19].…”
Section: Pl From Gainp Epilayers and Gainp/algainp Quantum Wellsmentioning
confidence: 66%
“…The degree of alloy ordering, expressed in terms of a mean order parameter Z; can be estimated from low-temperature PL data [17][18][19][20]. For perfect substitutional randomness Z is zero and for perfect (Cu-Pt type) long-range order Z ¼ 1: The bandgap shrinkage E g ð0Þ À E g ðZÞ and Z are related to each other: E g ðZÞ ¼ E g ð0Þ À Z 2 ½E g ð0Þ À E g ð1Þ:…”
Section: Pl From Gainp Epilayers and Gainp/algainp Quantum Wellsmentioning
confidence: 99%
“…3,4 Although the driving force for ordering is understood, the mechanism remains unknown; however, several speculative models have been proposed. 5 Besides the known role of surface reconstruction, surface steps may also be important factors in the ordering process.…”
mentioning
confidence: 99%
“…[8][9][10] Thus, in principle, a much more attractive approach would be to change the flow rate of the phosphorus precursor to produce the desired change in order parameter, although the changes in bandgap energy are typically considerably smaller than for changes in temperature. The initial attempts to produce heterostructures in this way used PH 3 as the P precursor at a growth temperature of 620°C.…”
Section: Growth Of Order/disorder Heterostructures In Gainp Using a Vmentioning
confidence: 98%
“…6 This has been demonstrated by the recent experimental observation, using surface photo absorption (SPA), that the concentration of 110 [ ] P-dimers on the (001) surface correlates closely with the degree of order (S) produced during OMVPE growth as the growth temperature and partial pressure of the P precursor (P P ) are varied. [7][8][9][10] It has been suggested that the step structure on the surface during growth may also play a role in the ordering process. [10][11][12] (Received March 13, 1997; accepted May 6, 1997)…”
Section: Introductionmentioning
confidence: 99%